Weiterentwicklung der Beleuchtungseinheit LED-basierter Projektionssysteme - Schulz, Benjamin (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2019)
This work deals with the maximum achievable output flux of LED-projectors which is limited by physics. With the objective of increasing the output flux further, the illumination unit of LED-based projectors is enhanced systematically by improving existing technologies and developing new concepts.